2009
DOI: 10.1590/s0102-695x2009000500016
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and bioactivity of leaves of Murraya paniculata (L.) Jack, Rutaceae

Abstract: RESUMO: "Antinociceptiva e bioatividade das folhas de Murraya paniculata (L.) Jack, Rutaceae". Os resultados dos estudos de atividade antinociceptiva e toxicológicos do extrato etanólico de Murraya paniculata (L.) Jack, Rutaceae são relatados. O extrato (nas doses de 250 e 500 mg/kg) produziu um alta atividade antinociceptiva na forma dose-dependente. O extrato também mostrou considerável toxicidade no teste de Artemia salina (DL50 = 32 µg/mL). Unitermos:Murraya paniculata, Rutaceae, contorções, analgesico, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
1
24
0
1
Order By: Relevance
“…At these two doses, the numbers of writhings were decreased, respectively, by 26.7 and 66.7%. In comparison, a standard antinociceptive drug, diclofenac, when administered at a dose of 25 mg/kg decreased the number of writhings by 82.7%, demonstrating that the leaves like the bark possesses phytoconstituents with significant pain-relieving potential [12].…”
Section: Analgesic and Anti-inflammatory Activitymentioning
confidence: 94%
“…At these two doses, the numbers of writhings were decreased, respectively, by 26.7 and 66.7%. In comparison, a standard antinociceptive drug, diclofenac, when administered at a dose of 25 mg/kg decreased the number of writhings by 82.7%, demonstrating that the leaves like the bark possesses phytoconstituents with significant pain-relieving potential [12].…”
Section: Analgesic and Anti-inflammatory Activitymentioning
confidence: 94%
“…However, medicinal use of leaves in decoction or infusion is the most common use, but other parts of the plant have been used traditionally as the bark and the roots. In China, M. paniculata was used to regulate fertility (Black, ), antinociceptive effect (Sharker et al, ), as potential therapeutic applications for treatment of toothache (Rahmatullah, ) and analgesic activity (Fazal‐ur‐Rehman et al, ) and antimicrobial activity (Menezes et al, ). These activities correlated positively with the presence of secondary compound classes.…”
Section: Introductionmentioning
confidence: 99%
“…A chemical study of this plant collected in São Paulo, Brazil, showed that it had a different chemical profile, when compared with studies using plant material collected in Asian countries. It is reported to have antinociceptive and antiinflammatory (Narkhede et al, ; Podder et al, ; Sharker et al, ), antidiarrheal (Rahman et al, ), and hypoglycemic effects (Gautam et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…So far the leaves of this plant have been proved to possess significant antinociceptive, antibacterial, antifungal, and antioxidant [1,2]. It is widely used and has a good curative effect on treating superficial gastritis, erosive gastritis and intestinal metaplasia [3].…”
Section: Introductionmentioning
confidence: 99%